Análise do comportamento de escolha e orientação profissional - Paixão, Heren Nepomuceno Costa (2020)
In the search for the understanding about factors that influence career choice, the objective of this work was both the development and implementation of a professional orientation, about the focus of behavior analysis, such as the evaluation of impact of career guidance on career choice. The research subjects were 16 third year high school students, who were in doubt as to their professional choice, separated into two groups, the Choice Group (GE) and the Group of Control (CG). In the pre-intervention session both groups were submitted to the Entry Questionnaire, plus the Variable Identification Questionnaire for the EG. Post intervention, both groups were exposed to the Exit Questionnaire, Consumer Satisfaction Inventory and Program Evaluation Questionnaire. In the specific meetings of the CG, the Self-knowledge Exercise, the Profession-Characteristic Combination Technique, the Investigation of the Professions with Informative Material, the Criteria Analysis Exercise of the Selection Criteria were conducted. For the GE in the specific meetings, the Matrix of Skills and Professional Interests was used, Relating characteristics and professions, Investigation of the professions through a program with choice of presentation videos of the professions. At follow-up, performed after one year of orientation, all participants were given the exit questionnaire and the variable identification questionnaire. The main results were that the main variables considered referred to the repertoire itself and the professions, both pre and post intervention. For both groups, CG and GE, the number of professions to be considered decreased. Regarding the position in relation to the choice, the CG remained with great difficulty or with difficulty and in the GE 90% considered themselves decided or have already made their choice. In addition, 90% of GE participants considered themselves to be more or less safe or extremely safe, and GC participants remained very insecure, insecure or more or less insecure. The program increased participants' variability in professional information and made them more discriminative in decision-making. The situation of video choice and the identification of variables may have contributed to greater effectiveness in GE compared to GC. This study contributed to the knowledge about the impact of career guidance on career choice and had practical implications for the development of career guidance programs that can support young people facing indecision in choosing a profession